Peran Akuntansi dalam Meningkatkan Transparansi Keuangan (Studi Kasus MTS AL - Husna Rahmat Jakarta) - Praptasari, Mutiara; Anggraini, Daz Vholasky (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The purpose of this study was to analyze the role of accounting in improving financial transparency at MTS AL-Husna Rahmat Jakarta through the implementation of a computer-based accounting system and the involvement of parents in managing school funds. using a qualitative approach with a case study at MTS AL-Husna Rahmat Jakarta to analyze the role of a computer-based accounting system and the involvement of parents in improving school financial transparency. Data were collected through interviews, documentation, and observations, which were analyzed using thematic techniques to identify the impact of transparent and accountable financial management. This study found that MTS AL-Husna Rahmat succeeded in improving financial transparency through the implementation of a computer-based accounting system that allows for accurate and efficient recording and reporting. Regular meetings with parents are also an important mechanism for openness of information and providing input related to fund management. Although there are challenges in training financial staff, routine training every three months has succeeded in overcoming technical obstacles. Quarterly financial reports and structured document storage demonstrate the school's commitment to transparency. Overall, the involvement of parents and a transparent system increase public trust in fund management at MTS AL-Husna Rahmat.